The threshold effects of income diversification on bank stability: an efficiency perspective based on a dynamic network slacks-based measure model - Ben Lahouel, Béchir; Taleb, Lotfi; Kočišová, Kristína; Ben Zaied, Younes (Annals of operations research, 2023)
This study examines whether nonlinear effects of income diversification on bank stability occurs in the European banking system. Based on the framework developed by Tone and Tsutsui (Omega 42(1):124–131, 2014), we propose a novel three-stage (deposit producing, intermediation, and value maximization) dynamic network slacks-based measure model to assess bank stability in a sample of 114 European commercial banks during the post financial crisis period (2010–2019). We use the panel smooth transition regression model (PSTR), as introduced by González et al. (Panel smooth transition regression models, CREATES research paper 2017-36. Department of Economics and Business Economics, Aarhus University, 2017), to investigate the potential regime-switching behavior of the relationship between income diversification and stability. Our findings show that higher levels of income diversification, into and within nontraditional banking generating activities, worsen bank stability. It results that, in the case of European banks, income diversification is sub-optimal as no benefits are found from “over diversification”. Important policy implications arise from our findings pertaining to the optimality of income diversification and stability, which could be in conflict with banks’ traditional lines of business aiming at promoting lending activities.